ACTUAL ISSUES OF GUARDIANSHIP AND TUITION - Nino Mindiashvili (European Scientific Journal, ESJ, 2016)
Collision issues are discussed in family law such as conditions of marriage, results of marriage, annulment of marriage, duty of maintenance, relations between parents and children, relations related to child’s origin, conditions of adopting, guardianship and tuition. I discuss issues of guardianship and tuition in mentioned work, which I think is very interesting and actual.